Bom bunuh diri dalam fatwa kontemporer Yusuf al-Qaradawi dan relevansinya dengan maqasid al-Shari’ah - Busyro Busyro (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2016)
All contemporary fatwas Yusuf al-Qaradawi in his book Min Hadyi al-Islam Fatawa Mu’ashirah was believed by the writer it made succeed maqasid al-shari’ah. When we see the fatwa in the book, some of fatwa indicate contradiction with maqasid al-shari’ah  which is agreed by most of islamic scholars, such as his fatwa about suicide bombing according to this problem, the axamination will ask after; how is law of thinking al-Qaradawi with suicide bombing? And how to aplicate the theory of maqasid al-shari’ah in  al-Qaradawi’s fatwa in suicide bombing? To answer the question, this examination tried to trial to the fatwa al-Qaradawi about it in the book by seeing the connected with theory of maqasid al-shari’ah  which is agreed by most of islamic scholars. For that the theory about maqasid al-shari’ah will be tested comprehensively, particulary to save al-daruriyat al-khams (five of human fundamental needs). The data has been collected and will be analysed qualitatively. The result of this examination made succeed the answer that al-Qaradawi pleases the action of suicide bombing specially for the fighters of Palestine to make fear and terrorist to Israel; and his fatwa opposite with maqasid al-shari’ah which believed the legitimate by most of islamic scholars.